Factors Affecting Place Attachment and Types of Living Arrangement Preferences for Ageing-In-Place of the Malaysian Generational Housing Consumers in Malaysia - Ismail, Hafiszah; Zainan Abidin, Aida Wati; Johaimi Ling, Nur Lesya Firsya; Afif, Aqilah Syauqina; Siahaan, Elisabet (International Journal of Sustainable Construction Engineering and Technology, 2023)
Nearly all older adults prefer to age in their homes and neighbourhoods instead of in an institutional facility. The concept of ‘ageing-in-place’ enables people to maximise their self-realisation and preferred lifestyle in familiar surroundings or elsewhere. The study aims to provide an in-depth overview of the place attachment factors and living arrangement structure preferences that affect the generations in Shah Alam, Selangor. The main objectives of this study are: (i) to identify the factors affecting place attachment for ageing-in-place; and (ii) to determine the types of living arrangement preferences for ageing-in-place. This study adopts a mixed-method research strategy combining qualitative (interviews with industrial experts) and quantitative (survey questionnaires to the housing consumers) data gathering. The findings from this study reveal four (4) main place attachment factors: (1) Facilities & Amenities; (2) Geographic Location; (3) Physical Environment; and (4) Social & Well-being. The main types of preferred living arrangement for ageing-in-place are; (1) Living alone; (2) Living with parents; (3) Living with spouse; (4) Living with son/daughter; and (5) Living with family members. The research findings are vital, where it can be beneficial to the actors of the development process, including the public and private agencies, to gain more knowledge on the preferences factors for ageing-in-place for a better supply of housing provisions. The housing consumers in Malaysia will benefit from having more housing choices specifically tailored for future ageing life stages.